2020
DOI: 10.1021/acs.est.0c03099
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to PFAS is Associated with Telomere Length Dynamics and Demographic Responses of an Arctic Top Predator

Abstract: Environmental factors that can influence telomeres are diverse, but the association between telomeres and exposure to environmental contaminants is yet to be elucidated. To date, prior studies have focused on legacy persistent chlorinated pollutants (POPs), while the effects of poly- and perfluoroalkyl substances (PFAS) have been poorly documented. Here, we investigated the associations among PFAS congeners, absolute telomere length (cross-sectional approach), and telomere dynamics (rate of telomere length cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…This is in agreement with recent studies conducted on PFASs in plasma samples of glaucous gull from Svalbard. 86,89 This observation has also been made for other Arctic biota, including sh, birds and mammals. 90 Long-range transport and degradation of FTOHs is assumed as a source for the observed long-chain PFCAs in arctic animals.…”
Section: Concentration and Distribution Patterns Of Pfas In Glaucous Gull (Larus Hyperboreus)mentioning
confidence: 64%
See 1 more Smart Citation
“…This is in agreement with recent studies conducted on PFASs in plasma samples of glaucous gull from Svalbard. 86,89 This observation has also been made for other Arctic biota, including sh, birds and mammals. 90 Long-range transport and degradation of FTOHs is assumed as a source for the observed long-chain PFCAs in arctic animals.…”
Section: Concentration and Distribution Patterns Of Pfas In Glaucous Gull (Larus Hyperboreus)mentioning
confidence: 64%
“…This agrees with recent studies where sex-related differences in PFAS concentrations were reported. 86,89 Since the gulls were sampled prior to breeding, it is likely that they have been exposed to and accumulated PFAS when feeding in their wintering grounds. Thus, the PFAS body burdens of the bird constitutes of a mixture of PFAS compounds that have accumulated during feeding in their unknown wintering grounds, and in the Adventord following their return to Svalbard.…”
Section: Concentration and Distribution Patterns Of Pfas In Glaucous Gull (Larus Hyperboreus)mentioning
confidence: 99%
“…In chicks of white-tailed eagles Haliaeetus 621 albicilla, no relationship between the concentrations of organohalogenated compounds (PCBs, DDT, 622 HCH, HCB: hexachlorobenzene) and TL was observed, despite significant changes in the antioxidant 623 enzyme superoxide dismutase, plasma non-enzymatic antioxidant capacity and oxidative damage to 624 plasma proteins (Sletten et al, 2016, Costantini et al, 2019. In contrast, in the adult glaucous gull 625 Larus hyperboreus, some single PFAS compounds are positively correlated with the slowest rate of 626 telomere shortening (Sebastiano et al, 2020). Similar to humans, the, contaminant effect on telomere 627 dynamics in birds seems to vary according to the nature of the contaminant and the species.…”
Section: Telomere Length Can Vary Under the Influence Of Environmenta...mentioning
confidence: 96%
“…So far, we lack key information on the causal relationship between specific disturbances and the organismal response in terms of telomeres. Moreover, we are in need of studies exploring the link between telomere length and individuals' fitness or performance in anthropogenically influenced scenarios, which has been done only recently in a handful of studies and with a mixed results (Kirby et al, 2019;Louzon et al, 2020;Salmón et al, 2017;Scholten et al, 2020;Sebastiano et al, 2020). Both are critical aspects for the broad implementation of telomeres in the estimation of ecological risk (Calow & Forbes, 1998;Forbes et al, 2006;Timbrell, 1998).…”
Section: Per S Pec Tive S On Telomere S a S B I Omark Er S Of The Eff...mentioning
confidence: 99%